No need to rewrite education blueprint - Abd Razak, Dzulkifli (2008)
FORMER Minister of Higher Education Datuk Mustapa Mohamed is moving to the Agriculture and AgroBased Industry Ministry. Although he was in charge for only two years, To' Pa managed to endear himself not only in words but also in his actions. When he took over as the second minister of the just established ministry, it was in the midst of uncertainties. Within a short period, the situation stabilised. Animosities and suspicions that coloured the atmosphere gradually disappeared. Just like the firstclass scholar he is, the minister picked up fast the major issues plaguing the higher education sector.